Kelekatan Anak Keluarga Tenaga Kerja Wanita - Fatkhurohmah, Dian; Karim, Muhammad Busyro; Nisa, Titin Faridatun (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine the attachment of children in the family of female workers in father’s parenting style, social interaction of children with mothers, and attachment of children to mothers. This research wan conducted in the village of sumbersari, Udanawu District, Blitar Regency. East Java. It is consisting of two families which were used as research, there are 4 informants (2 fathers and 2 relatives) and 2 boys. This study used a qualitative approach, with descriptive methods. Data collection techniques used observation, interview, and documentation techniques. This research used data analysis procedure of Miles and Hubermen. The results explain that the form of parenting given by the father to the child according to the stage of child development. The attachment of children to women in the status of female workers showed a difference between the two subjects. The first subjects had attachment to the mother, while the second subject lacked attachment to the mother. The social interaction between mother and child also goes well.